Digital-Based Informal Entrepreneurship Education: Transforming Social Media into a Business Learning Space - Nurhayani, Nurhayani; Isma, Andika; Windarsari, Wiwin Riski; Alisyahbana, Andi Naila Quin Azisah; Muflih, Betania Kartika (Journal of Economic Education and Entrepreneurship Studies, 2025)
The development of digital technology has driven transformations in various aspects of life, including entrepreneurship education. This study examines how social media can be utilized as an informal learning space to support digital-based entrepreneurship education without being limited by space and time. Using a qualitative approach and literature review, this article explores the role of platforms such as Instagram, TikTok, and YouTube in disseminating entrepreneurial knowledge, building business communities, and creating flexible and accessible learning ecosystems. The results show that social media is not only a means of business promotion but also plays a role as an interactive and inspiring educational medium. The use of experience-based content, tutorials, and entrepreneurial success stories is a key strategy in educating audiences, both informally and formally. This article recommends optimizing the use of social media by educators, MSMEs, and entrepreneurial communities to expand access to relevant and contextual business learning in the digital era.